Acute electrical and hemodynamic effects of endocardial biventricular pacing using the WiSE CRT system and conventional epicardial biventricular pacing. Issue 1 (21st December 2017) - Leo, Milena; Webster, David; Betts, Tim R.
Abstract: Wireless left ventricular endocardial pacing with the WiSE CRT system has recently become available as alternative to conventional epicardial CRT pacing. We report the first comparison of the acute electrical and hemodynamic response produced by the two CRT pacing modalities in a patient undergoing WiSE CRT implant after a failed conventional CRT procedure. WiSE CRT pacing showed an additive acute benefit compared with conventional CRT. These findings could potentially translate into long‐term clinical benefit and introduce the potential for tri‐ventricular pacing using both systems simultaneously.